Calcined Mytella falcata shells as alternative adsorbent for efficient removal of rifampicin antibiotic from aqueous solutions. Issue 3 (June 2020) - Henrique, Daniely Carlos; Quintela, Daniel Uchoa; Ide, Alessandra Honjo; Erto, Alessandro; Duarte, José Leandro da Silva; Meili, Lucas
Graphical abstract: Abstract: This work deals with the use of Mytella falcata shells (a bivalve mollusk) as innovative biosorbent for the removal of rifampicin antibiotic from water. The material is alternatively tested as raw or after either pyrolysis or calcination, in order to improve its adsorption capacity. The calcination temperature (700 °C) was determined from the thermogravimetric analysis (TGA) of the raw shell. Preliminary adsorption tests allow individuating the calcined sample as the most performing. Scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and X-ray-dispersive energy spectroscopy (EDS) are used for characterization of the adsorbent. They showed the presence of residual CaCO3, mainly in the form of aragonite and calcite, and a porous structure with heterogeneous surface characterized by rounded particles. Kinetic tests showed fast adsorption phenomena, which were completed in 30−45 min. They present the best fit with pseudo-first order model and the equilibrium adsorption capacity obtained in the different tests (3.05, 4.58 e 7.00 mg.g −1 ) were satisfactorily predicted. Equilibrium data show that rifampicin adsorption capacity is almost independent on temperature, probably for the simultaneous increase in water desorption associated with the increase in temperature. The isotherms show a Redlich-Peterson model behavior, indicating a multilayer adsorption. The analysis of thermodynamic parameters shows that adsorption is spontaneous and slightly endothermic. Further experimental tests to simulate different water matrix indicate that a high ionic strength can increase the adsorption of rifampicin on the selected adsorbent. Finally, adsorbent regeneration by sonication shows a significant decrease in the performances after 5 adsorption/desorption cycles.